A New Space-Vector-Modulation Algorithm for a Three-Level Four-Leg Npc Inverter - Rojas-Lobos, F (Institute of Electrical and Electronics Engineers Inc., 2017)
For power conversion systems interfaced to four-wire supplies, four-leg converters have become a standard solution. A four-leg converter allows good compensation of zero-sequence harmonics and full utilisation of the dc-link voltage. These are very important features when unbalanced and/or nonlinear loads are connected to the system. This paper proposes a three-dimensional space vector modulation (SVM) algorithm and provides a comprehensive analysis of the algorithm implemented on a three-level, four-leg neutral-point-clamped converter. The algorithm allows a simple definition of the different switching patterns and enables balancing of the dc-link capacitor voltages using the redundancies of the converter states. A resonant controller is selected as the control strategy to validate the proposed SVM algorithm in a 6 kW experimental rig. © 2016 IEEE.